Pengaruh Kualitas Produk, Persepsi Harga, dan Lokasi terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian di Mcdonald`s - Muhammad Rizky Fathoni; Darwin Raja Unggul Saragih (Universitas 17 Agustus 1945, 2024)
This study aims to analyze the effect of product quality, price perception and location on customer satisfaction through purchasing decisions. The object of research on McDonald's Cibinong with the number of population or customers who have made purchases more than twice. Data collection techniques, purposive sampling methods and data processing with SmartPls on a total of 200 respondents. The results of this study show that product quality has a significant impact on customer satisfaction and purchasing decisions have a significant impact on customer satisfaction through purchasing decisions. Price perception has a significant impact on customer satisfaction, purchasing decisions have a significant impact on customer satisfaction through purchasing decisions, and location is not significant on customer satisfaction but has a significant effect on purchasing decisions and has a significant effect on customer satisfaction through purchasing decisions, purchasing decisions have a significant impact on customer satisfaction.